Perancangan Basis data Pajal Bumi Dan bangunan Sektor Perhutanan menggunakan Perangkat Lunak Oracle - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran (UI2P2) Universitas Gadjah Mada, 2003)
, The fOrestry sector is one Of the significant sectors that contribute to the state tax revenue, especially through PBB (bid and Budding lax). To- date, the PBB data of the prestrï®â¢ sector has been done manually. Therefore, the research is directed ) design a computerized P118 data of the forestry sector database, and (2) integrate the result with the SISMIOP (Property Tax lnlarmation and Management System) database to be an inï´emted tax management information system. The research began with the preparation. including data inventory and evaluation, enterprise rules development, entity relationsInpthogram development, data modelling development based on both conceptual and physical data modelling, and an application prOgralll model design. The research was .completed wish the analysis all tables in the database developed in the- design stage ',omen to make sure that all items of the data are complied with the defined rules and requirements. The analysis of the results comprised perfinmance frit database evaluation, and integrated with SISMIOP database